Navigating The Complexity Of Arabic Language Learning: A Conceptual Model Of Madrasah Tsanawiyah Students' Experiences - Muzakki Abdurrahman (JURNAL IJ-ATL, 2026)
Arabic language learning remains challenging for many students due to its linguistic complexity and its influence on cognitive and emotional learning experiences. This study aims to explore how Madrasah Tsanawiyah students navigate the complexity of Arabic language learning and to develop a conceptual model based on their lived experiences. Employing a qualitative phenomenological approach, data were collected from 12 purposively selected ninth-grade students through in-depth interviews, classroom observations, and document analysis. The findings revealed four interconnected stages of experience: initial confusion (50%), adaptation process (33%), and survival strategies (17%), with nahwu and sharaf identified as the dominant learning difficulties (50%), followed by vocabulary (30%) and instructional factors (20%). Students also experienced anxiety and low self-confidence while developing coping strategies through peer discussions, vocabulary memorization, and digital learning resources. The study contributes a conceptual model integrating cognitive, affective, and behavioral dimensions and recommends more adaptive and student-centered Arabic language instruction.